SKACICM a method for development of knowledge management and innovation system e-KnowSphere. (2015) - Aitouche, Samia; Mouss, Mohamed Djamel; Kaanit, Abdelghafour; Bouhafna, Khayreddine; Mammeri, Walid; Chabbi, Abdeldjalil
The purpose of this paper is to propose a hybrid method SKACICM of development of knowledge management systems. Based on weaknesses of the method of performance dashboards SKANDIA, we proposed a pragmatisation and adaptation of Skandia to give (ASKANDIA), by enrichment of its performance book. We ameliorated CICM model against the requirements of GERAM to give ACICM model by mappings between their proposed metamodels. We tried to hybridise ACICM, ASKANDIA and business intelligence to propose a new method SKACICM of development of knowledge management systems. We applied SKACICM on a cement company to develop software containing three main modules, module knowledge management, module business intelligence and performance dashboard system. The developed system ameliorated the performance of the enterprise by 26% and could be generalised to other manufacturing or service systems.